Optimum Tilt Angles for PV Modules in a Semi-Arid Region of the Southern Hemisphere - E Hertzog, Pierre; J Swart, Arthur (International Journal of Engineering and Technology, 2018)
It is essential to repeat a test of a given construct in research in order to underpin knowledge, support validity and enable its application in other contexts. The purpose of this article is to present repetitive test results validating the optimum tilt angle of a stationary PV module that was installed in a semi-arid region of South Africa. An experimental design incorporating a two-year longitudinal study is used. The results for 2016 and 2017 reveal that a PV module with a tilt angle of Latitude plus 10Â° yielded the highest output power for winter months, while a PV module with a tilt angle of Latitude minus 10Â° yielded the highest output power for summer months. However, for both years, a tilt angle set to the Latitude angle of the installation site yielded the highest overall average output power (60.02 Wh per day). It is therefore recommended to install stationary PV modules at a tilt angle equal to the Latitude of the installation site for a semi-arid region in the southern hemisphere.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â